Implementasi Konsep Belajar Kognitivisme dalam Mata Pelajaran IPA Sekolah Dasar - Mita Ervina (Bidayatuna, 2018)
The low pedagodic ability of the teacher affects in carrying out a practical learning activity in class V SDN Barat 02 Padang, Lumajang and learning with lecture model and assignments carried out by the teacher during the learning delivery process taking place at SDN BARAT 02 Padang, Lumajang. This study used a qualitative descriptive method. Data collection techniques used observation, interviews and document study. This study shows the concept of learning cognitivism, which is a learning process involving mental activities in students and the implementation of the concept of learning cognitivism through practicum in science subjects in class V SDN Barat 02 Padang, Lumajang.Teachers make preparations for various things, from the material that will be delivered until the material used for practice and things important during the learning process.